Does Early Embryogenesis in Eudicots and Monocots Involve the Same Mechanism and Molecular Players?. Issue 1 (1st December 2016) - Zhao, Peng; Begcy, Kevin; Dresselhaus, Thomas; Sun, Meng-Xiang
Abstract : A comparison of eudicot and monocot model plants explores recent advances and open questions on gene regulatory networks during zygote development, parental influences on early embryogenesis, zygotic genome activation, and cell fate determination.